Roof Replacement of a Heritage Building Using Transparent Solutions: Room Acoustic Performance Comparison - António P. O. Carvalho (2020)
Tensile membrane roofs are considered to have the potential to improve the buildings' performance due to their lightweight and flexible nature. However, their potential for improving acoustic behaviour has hardly been accurately gauged or demonstrated due to their complexity in both geometric and physical aspects. To address this issue, Carmo's church in Lisbon-a heritage building that lost the roof during the 1755 earthquake and is nowadays a museum-was selected as case study to analyse the impact of covering high complex volumes in room acoustics by using a conventional and an alternative transparent solution: (i) a single glazing and (ii) a simple and transparent ETFE membrane tensioned in a self-supporting metal structure. This last solution is combined with a retractable cross-vaulted ceiling in a translucent and acoustic absorbent membrane supported by pneumatic ribs. The acoustic performance for music and speech emission of these two options is compared to each other and to the existing scenario-without roof-through numerical modelling and by considering a set of selected parameters: Reverberation Time, Clarity, Early Decay Time, Speech Transmission Index and Definition (D-50). These analyses allowed verifying the potential of membrane solutions to improve the acoustics of high complex volumes.